Skenario Peningkatan Pertumbuhan Ekonomi Berbasis Tingkat Pengeluaran Wisatawan di Provinsi Nusa Tenggara Barat (Pendekatan Sistem Dinamis) - Widayanti, Baiq Harly; Wilantari, Regina Niken; Viphindrartin, Sebastiana; Zainuri, Zainuri (Jurnal Samudra Ekonomi dan Bisnis, 2025)
The tourism sector is one of the most important sectors in enhancing economic growth, as it has a significant multiplier effect on various other economic activities. Tourist expenditures serve as a key indicator of the tourism sector's impact on society. These expenditures contribute significantly to local income sources and regional economic growth. Therefore, this research aims to formulate an economic growth scenario model based on tourist expenditure levels in West Nusa Tenggara Province (NTB). A dynamic system analysis method is employed to comprehensively examine all related variables and their interdependencies. This study produces an optimal scenario involves implementing policies to increase tourist visits, as this not only directly affects economic growth but also influences tourists' length of stay and total expenditure.